Democracia política como plataforma para a expansão de direitos na América Latina - Maria Celina D\u2019Araujo (Ciências Sociais Unisinos)
This article outlines macrossociological aspects of recent changes in Latin America that strengthen democratic points from the institutional point of view. The issue of human rights, security and gender, the region is far beyond the modern European democracies, but a tendency, even with occasional setbacks, is a transformation favorable to good practices of greater equality and appreciation of formal democracy. Trouble spot continues to be inequality and interpersonal violence, while local companies are obliged to give warning signals to the importance of universals for justice and equity. The article draws attention to some transformations that impact on the areas of law and democratization and the possibilities of political participation, especially the feminine. The election of conservative governments in the second decade of the twenty-first century, after the so-called “pink wave,” has not, as yet, nullified the recognition of democracy and the rule of law as “the only game in town.”